Multimedia Data Mining- A Survey (International Journal of Engineering and Computer Science, 2014)
In the recent years, data quarrying or mining has been an effective as well as powerful approach for extracting concealed knowledge from huge collections of regulated digital data stored in databases. From the inception, data mining was being done predominantly on the numerical set of data. Nowadays as large multimedia data sets such as audio, speech, text, web, image, video and combinations of several types are becoming increasingly available, and are almost unstructured or semi-structured data by nature, it difficult for us to extract the information without powerful tools. This drives the need to develop data mining techniques that can work on all kinds of data such as documents, images, and signals. This paper sightsees survey of the current state of multimedia data mining and knowledge discovery, data mining efforts aimed at multimedia data, current approaches and well known techniques for mining multimedia data.